Facilitating sustainable professional part-time work: A question of design?. (29th July 2015) - Smith, Natalie; McDonald, Paula
Abstract: Despite significant socio-demographic and economic shifts in the contours of work over the past 40 years, there has been surprisingly little change in the way work is designed. Current understandings of the content and structure of jobs are predominantly underpinned by early 20th century theories derived from the manufacturing industry where employees worked independently of each other in stand-alone organisations. It is only in the last 10 years that elaborations and extensions to job/work design theory have been posed, which accommodate some of the fundamental shifts in contemporary work settings, yet these extended frameworks have received little empirical attention. Utilising contemporary features of work design and a sample of professional service workers, the purpose of this study is to examine to what extent and how part-time roles are designed relative to equivalent full-time roles. The findings contribute to efforts to design effective part-time roles that balance organisational and individual objectives.